Credit, prices, and crashes: business cycles with a sudden stop - Mendoza, Enrique G. (2001)
The 1990s emerging-markets crises were characterized by sudden reversals in inflows of foreign capital followed by unusually large declines in current account deficits, private expenditures, production, and prices of nontradable goods relative to tradables. This paper shows that these Sudden Stops can be the outcome of the equilibrium dynamics of a flexible-price economy with imperfect credit markets. Foreign debt is denominated in units of tradables and a liquidity constraint links credit-market access to the income generated in the nontradables sector and the relative price of nontradables. Sudden Stops occur when real shocks of foreign or domestic origin, or policy-induced shocks make this constraint binding. Sudden Stops are not reflected in long-run business cycle statistics but still they entail nontrivial welfare costs. These results question crises-management policies seeking to impose direct controls on private capital flows and favor those that work to weaken credit frictions.